2015
DOI: 10.1016/j.jlp.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Particle size and surface area effects on explosibility using a 20-L chamber

Abstract: The Mine Safety and Health Administration (MSHA) specification for rock dust used in underground coal mines, as defined by 30 CFR 75.2, requires 70% of the material to pass through a 200 mesh sieve (<75 µm). However, in a collection of rock dusts, 47% were found to not meet the criteria. Upon further investigation, it was determined that some of the samples did meet the specification, but were inadequate to render pulverized Pittsburgh coal inert in the National Institute for Occupational Safety and Health (NI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 8 publications
(19 reference statements)
0
11
0
Order By: Relevance
“…For coal, the complex refractive index has both a very significant imaginary component (it is strongly absorbing) and is not well characterized. It was taken as 1.80 + 0.3 i as previously reported (Harris et al, 2015). This complex refractive index for bituminous coal is also cited by Menguc et al (1994).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For coal, the complex refractive index has both a very significant imaginary component (it is strongly absorbing) and is not well characterized. It was taken as 1.80 + 0.3 i as previously reported (Harris et al, 2015). This complex refractive index for bituminous coal is also cited by Menguc et al (1994).…”
Section: Methodsmentioning
confidence: 99%
“…Past studies (Amyotte et al, 1995; Amyotte, 1996; Dastidar et al, 2001; Cashdollar and Hertzberg, 1985; Cashdollar et al, 1987, 1989; Cashdollar, 1996, 2000; Harris et al, 2015; Cybulski, 1975; Man and Harris, 2014; Rice, 1911; Rice et al, 1927a, 1927b; Richmond et al, 1975; Sapko et al, 2000) have shown the influence of coal's volatility and particle size on its explosibility and rock dust inerting requirements. Such studies led to the formulation of the initial legal requirement that mine dust in bituminous coal mines (anthracite mines are exempted due to their much lower volatility) must have an inert content of at least 65% in entries and 80% in air return passageways (CFR, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although rock dust products are not generally considered to pose health hazards, from an operational perspective, this issue is of increasing importance given that the total respirable dust concentration limit in US coal mines has just been reduced [58]. Moreover, recent research has suggested that finer rock dust products, which presumably contain even higher respirable fractions, should be more effective in reducing explosibility hazards [59].…”
Section: %mentioning
confidence: 99%
“…Coal particles less than 75 μm (minus 200 mesh) in size are most reactive and rock dust greater than 75 microns are much less effective in inerting (Man and Harris, 2014). Therefore, the application of appropriately sized and dispersible rock dust in sufficient quantities is essential to inert coal dust explosions and prevent continued flame propagation (Hartman et al, 1954; Cybulski, 1975; Sapko et al, 1987a, 1987b, 1998; NIOSH, 2010; Harris et al, 2015). The precise mechanism by which rock dust (generally pulverized limestone dust) quenches flame has not been fully explained, but is believed to involve absorption of thermal energy from the heated gases and absorption of radiant energy, which reduces the preheating of unburned coal particles ahead of the flame front.…”
Section: Introductionmentioning
confidence: 99%